2022
DOI: 10.1021/acsinfecdis.2c00165
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Characterization of SARS-CoV-2 nsp13 ATPase Activity and Discovery of Small-Molecule Inhibitors

Abstract: SARS-CoV-2 non-structural protein 13 (nsp13) is a highly conserved helicase and RNA 5′-triphosphatase. It uses the energy derived from the hydrolysis of nucleoside triphosphates for directional movement along the nucleic acids and promotes the unwinding of double-stranded nucleic acids. Nsp13 is essential for replication and propagation of all human and non-human coronaviruses. Combined with its defined nucleotide binding site and druggability, nsp13 is one of the most promising candidates for the development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Disulfiram is known as a “zinc-ejector” and has been shown to specifically target conserved zinc-bound cysteine residues [ 125 , 126 ]. This mechanism allows it to target the highly-conserved non-structural proteins nsp13 and nsp14 [ 128 ], critical enzymes that function in viral replication as a helicase [ 129 ] and an exoribonuclease, respectively. A study of disulfiram against viral pseudo-particles (Vpps) of multiple SARS-CoV-2 strains showed that disulfiram potently blocked viral entry via the inhibition of the interaction between the spike protein and its ACE2 receptor [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…Disulfiram is known as a “zinc-ejector” and has been shown to specifically target conserved zinc-bound cysteine residues [ 125 , 126 ]. This mechanism allows it to target the highly-conserved non-structural proteins nsp13 and nsp14 [ 128 ], critical enzymes that function in viral replication as a helicase [ 129 ] and an exoribonuclease, respectively. A study of disulfiram against viral pseudo-particles (Vpps) of multiple SARS-CoV-2 strains showed that disulfiram potently blocked viral entry via the inhibition of the interaction between the spike protein and its ACE2 receptor [ 130 ].…”
Section: Resultsmentioning
confidence: 99%
“…Structural, crystallographic, and mechanistic studies have identified two pockets where ATP and RNA bind [ 83 ]. These pockets and ATPase activity have been the target of multiple studies, resulting in several drugs and metabolites having the potential to bind to them, reducing the activity of NSP13 helicase [ 83 , 84 ]. Moreover, studies by Sui et al [ 85 ] showed that NSP13 is capable of inhibiting the production of type I IFN, allowing the virus to evade the innate immune response, shedding lighter on the importance of this protein in the pathogenesis of the virus and reinforcing its potential as a therapeutic target.…”
Section: Resultsmentioning
confidence: 99%
“…SARS-CoV-2 Nsp13 helicase is less studied, especially in comparison to the main protease (Mpro, or 3CLpro), and there are relatively few known inhibitors of SARS-CoV-2 Nsp13 helicase, and even fewer belonging to SAR, as summarized in Table S2 [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Inhibitors including repurposed drugs were shown to bind the SARS-CoV-2 Nsp13 helicase ATP binding site in recent studies [ 24 , 53 ]. Following Molecular Dynamics simulations (MDS) for in silico validation of target specificity, antiviral activity of N -functionalized 2-aminocyclobutanone hits and analogs was confirmed in vitro using a cell survival assay, and inherent cellular toxicity was assessed.…”
Section: Discussionmentioning
confidence: 99%